High-Cost Democracy: Stimulus Ijon Politik dalam Pemilu Lokal di Region Kaya Sumber Daya Alam - Hendy Setiawan; Maulida Rita Widyana (Jurnal Adhyasta Pemilu, 2022)
This study discusses the practice of political bondage which is increasingly prevalent in various regions in Indonesia. Actually, the cause of political bondage is due to high cost democracy which causes prospective candidates to have to look for sponsors, especially in companies that manage natural resources. So, when the candidate is elected or has officially taken office, he must fulfill the promise that has been agreed between the authorities and the entrepreneur, which promise can be in the form of mining permits, transfer of land functions, and so on. Then, the method used in this research is descriptive qualitative by explaining that political bonds have a correlation with corruption. Then, the researcher uses Ross' main theory which relates the correlation between natural resources that will hinder and hurt democracy. Then, Billon's theory is that natural resources have the ability to motivate and fund various forms of activity. The results of this study show that the existence of political bonds is highly correlated with corruption, because the authorities justify or make something illegal to be legal due to an agreement with businessmen. The corruption of natural resources that dominates the most is in the Pilkada, especially in areas that are rich in natural resources. Entrepreneurs actually also take advantage of the momentum of the Pilkada to be able to enter the gap so that all permits related to natural resources run smoothly and they are protected by the law in their respective regions.